Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (Washington, DC, 2015)
Palestinians are getting poorer on average for the third year in a row. As evidenced in previous World Bank reports, the competitiveness of the Palestinian economy has been progressively eroding since the signing of the Oslo accords, in particular its industry and agriculture. Even though donor aid had increased government-funded services and fueled consumption-driven growth during 2007 to 2011, this growth model has proved unsustainable. Donor support has significantly declined in recent years and, in any case, aid cannot sustainably make up for inadequate private investment. Thus, growth has started to slow since 2012 and the Palestinian economy contracted in 2014 following the Gaza war. In early 2015, GDP was still lower than it was a year ago. Due to population growth, real GDP per capita has been shrinking since 2013. Unemployment remains high, particularly amongst Gaza’s youth where it exceeds 60 percent, and 25 percent of Palestinians currently live in poverty. Against the backdrop of weak economic growth, reduced donor aid, and temporary suspension of revenue payments by the Government of Israel (GoI), the Palestinian Authority’s reform efforts have not been able to prevent another year with a financing gap. The persistence of this situation could potentially lead to political and social unrest. In short, the status quo is not sustainable and downside risks of further conflict and social unrest are high.